2004
DOI: 10.1039/b313798h
|View full text |Cite
|
Sign up to set email alerts
|

Highly diastereoselective formation of C2-symmetric bis-thioglycoside Pd(ii) complexes: the role of the exo anomeric effect

Abstract: Treatment of several C(2) symmetric bis-thioglycosides with Pd(CH(3)CN)(2)Cl(2) always leads to a single diastereomeric Pd(II) complex as a consequence of the exo-anomeric effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Upon coordination to the palladium, the chemical shifts of protons H-2, H-3, and H-6,6Ј do not change significantly, while proton H-5 and the protons α to the sulfur atom are deshielded by 0.1 ppm to 0.4 ppm. Significantly, the anomeric protons of the Pd II complexes are highly deshielded, by 0.6 to 0.8 ppm in the case of the five-membered palladacycles (23)(24)(25)(26)(27)(28) and by up to 1 ppm in the case of the six-membered palladacycle 29. In the 13 C NMR spectra the most significant change corresponds to the deshielding of the carbon α to the sulfur atom by 3 to 4 ppm.…”
Section: Mechanistic Considerationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Upon coordination to the palladium, the chemical shifts of protons H-2, H-3, and H-6,6Ј do not change significantly, while proton H-5 and the protons α to the sulfur atom are deshielded by 0.1 ppm to 0.4 ppm. Significantly, the anomeric protons of the Pd II complexes are highly deshielded, by 0.6 to 0.8 ppm in the case of the five-membered palladacycles (23)(24)(25)(26)(27)(28) and by up to 1 ppm in the case of the six-membered palladacycle 29. In the 13 C NMR spectra the most significant change corresponds to the deshielding of the carbon α to the sulfur atom by 3 to 4 ppm.…”
Section: Mechanistic Considerationsmentioning
confidence: 98%
“…X-ray analysis of complex 25 shed light on the origin of the stereochemical outcome of the reaction. [28] Compound 25 has an overall C 2 symmetry with the sugars in a pseudoaxial orientation, while the sulfur atoms both have (S) absolute configurations. Interestingly, the bulky Pd(Cl 2 ) group is anti to the C2 and to the C2Ј carbons (carbohydrate numbering) of the pyranose rings.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…If all of these are catalytically active, low selectivity can ensue as for each diastereomeric complex the preferred transition state may have a different geometry 27. Surprisingly, even though ligand 70 appears conformationally very flexible at first glance, only one complex was detected in solid state as well as in solution 28. The same group also described 2‐phosphinite‐thioglycoside ligand 71 based on D ‐galactose and its pseudo‐enantiomer ps ent ‐ 71 derived from D ‐arabinose 29.…”
Section: Carbohydrate Ligandsmentioning
confidence: 99%
“…9 In the case of phosphinite thioglycosides I metal complexes, where the exo-anomeric effect is not operative, good stereocontrol of the sulfur atom is also predicted taking into account the strong steric and stereoelectronic interactions of the substituent at sulfur and the endocyclic oxygen of the pyranose ring.…”
mentioning
confidence: 99%
“…8 A subsequent study of the corresponding Pd(II) complexes has indicated that the good enantioselectivity achieved was a consequence of an efficient stereocontrol of the sulfur atom exerted by the exo-anomeric effect. 9 In the case of phosphinite thioglycosides I metal complexes, where the exo-anomeric effect is not operative, good stereocontrol of the sulfur atom is also predicted taking into account the strong steric and stereoelectronic interactions of the substituent at sulfur and the endocyclic oxygen of the pyranose ring. Condensation of a thiol with galactose pentaacetate (1) in the presence of boron trifluoride afforded the corresponding thioglycosides 2-4 in high chemical yields (85-95%, Scheme 2).…”
mentioning
confidence: 99%